The Role of Customer Orientation, Competitor Orientation, and Marketing Strategy on Marketing Performance Coffee Shop & Coworking Space in Yogyakarta - Sella Oktiansyah; Audita Nuvriasari (Penerbit Jurnal Indonesia, 2025)
This research aims to analyze the role of Customer Orientation, Competitor Orientation, and Marketing Strategy on the Marketing Performance of Coffee Shop & Coworking Space in Yogyakarta. The sample in this study were 40 respondents. The sampling technique used a non-probability sampling method with the research instrument used was a questionnaire. The results of the instrument test state that the data in this study are proven to be valid and reliable. The classical assumption test states that the data in this study are normally distributed and produce a regression model that is free from multicollinearity and heteroscedasticity. The findings of the results of this study prove that: (1) Customer Orientation has a positive and significant effect on the marketing performance of Coffee Shop & Coworking Space in Yogyakarta, (2) Competitor Orientation has no effect on the marketing performance of Coffee Shop & Coworking Space in Yogyakarta, (3) Marketing strategy has no effect on the marketing performance of Coffee Shop & Coworking Space in Yogyakarta.